2014
DOI: 10.1534/g3.114.011338
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Analysis and Association Study Identifies Loci for Polydactyly in Chickens

Abstract: Polydactyly occurs in some chicken breeds, but the molecular mechanism remains incompletely understood. Combined genome-wide linkage analysis and association study (GWAS) for chicken polydactyly helps identify loci or candidate genes for the trait and potentially provides further mechanistic understanding of this phenotype in chickens and perhaps other species. The linkage analysis and GWAS for polydactyly was conducted using an F2 population derived from Beijing-You chickens and commercial broilers. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Based on the 60 K SNP chip, the previous study identified 7 SNPs associated with the chicken polydactyly (Sun et al, 2014). As mentioned above, we both detected an association signal within the intergenic region between LMBR1 and SHH.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Based on the 60 K SNP chip, the previous study identified 7 SNPs associated with the chicken polydactyly (Sun et al, 2014). As mentioned above, we both detected an association signal within the intergenic region between LMBR1 and SHH.…”
Section: Resultssupporting
confidence: 54%
“…associated with the chicken polydactyly condition (Dorshorst et al, 2010). The intergenic region is of particular interest because a polymorphism Gga_rs14135036 located here also showed an association with the chicken polydactyly in a previous study (Sun et al, 2014). The SNP rs313965877, located intronic to RNA binding motif protein 33 (RBM33) gene, was identified to be significantly associated with the disorder phenotype (P = 2.39 × 10 −7 ).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Foeger et al (2012) found that heterologously expressed DPP6 localizes to the cell surface in the absence of Kv4.2 in mouse cortex (23) while Nadin and Pfaffinger (34) reported that DPP6 interacts with the K2P channel TASK-3 to regulate resting membrane potential and input resistance in cerebellar granule cells (34). Moreover numerous genome-wide association screens for a variety of maladies implicate a potential role for DPP6 (26,27,35,36). Further studies will be required to determine which DPP6 domains are responsible for its various functions but it seems likely that its role in regulating filopodia involves an interaction between its ␤-propeller structure located in the cysteine-rich domain and the extracellular matrix protein fibronectin (11) as found for DPPIV (10) (37).…”
Section: Dpp6 Domains Responsible For Its Interaction and Function Inmentioning
confidence: 99%
“…,b), polydactyly (Sun et al . ) and physical appearance traits (accept from G3). In the present study, our aim was to identify potential loci and candidate genes affecting immune traits using the F2 resource population.…”
Section: Introductionmentioning
confidence: 99%